Morphological and molecular characterisations of Phytophthora palmivora infecting cocoa in Pahang and Perak, Malaysia - Alsultan, Wael M. K. (2015)
Phytophthora spp. are one of the most destructive plant pathogens worldwide. Many economically important crop species such as cocoa, rubber, jackfruit, durian, taro, papaya, pepper, coconut, potato, citrus and forest trees are susceptible to various diseases caused by Phytophthora spp. Agronomists and plant pathologists have been aware of the economic importance of diseases caused by Phytophthora in Southeast Asia. However, there is a lack of published information on Phytophthora spp. in the tropics. Although many studies have been conducted over the past few decades to overcome diseases caused by Phytophthora spp., the general information is often not outlined with details while specific information of occurrence and economic impact are dispersed in many different publications in various languages. Black pod disease of cocoa caused by Phytophthora palmivora is a serious problem of economic importance to cocoa growers in Malaysia. It is also known to cause stem canker disease where their control in infected cocoa plantations is very difficult. This research was undertaken to study the cultural characteristics, reproduction, and pathogenicity as well as molecular characteristics of fourteen isolates of Phytophthora spp. randomly obtained from infected cocoa pods in two different states, Pahang and Perak in Peninsular Malaysia. The cultural characteristics of these isolates were assessed on four types of agar medium namely PDA , CA, VJA and CMA incubated at 25 ± 2°C showed various textures of colonies as fluffy with irregular margin on PDA, cottony with uniform margin on CA, slightly cottony with regular margin on VGA and flattish with regular margin on CMA. It did not show specific colony pattern on all four types of medium and each medium demonstrated its own morphological appearance. Growth rates of colonies were measured after three days of incubation on four types of agar media for one week and demonstrated that isolates grew significantly faster on CMA with 13.3mm/day, followed equally by VJA and CA with 10.0 and 10.2mm/day respectively, and the poorest growth was on PDA with 6.1mm/day. Dimensions of sporangia on CMA medium were measured averaging 43.48μm in length, 29.37 μm in width, 3.53 μm in pedicel length and 5.31 μm in size of exit pore. On culture media, the sporangia were of different shapes. Sporangia of isolates were all caducous. Zoospores were induced on four types of medium CA, VJA and CMA. Isolates on CA medium produced the largest number of zoospores than on VJA and CMA medium. Chlamydospores were produced on VJ broth ranging between 25.21 to 21.55 μm in diameter. Molecular identification using ITS region of rDNA confirmed that all isolates were Phytophthora palmivora. Eight isolates were selected randomly for pathogenicity tests on green healthy pods of KKM22 cocoa cultivar. The test results confirmed that isolates RB03 and RB04 from Pahang significantly more virulent with size of lesion 129mm and 117.75mm correspondingly compared to other isolates after five days of inoculation. Hence, complete brown to black lesions covered all inoculated after nine days.